Analyzing the transition from face-to-face to remote education: an experience in higher education during the COVID-19 pandemic - Jaramillo-Baquerizo, Christian (2021)
ICT integration has become one of the most crucial areas of research in education especially during the COVID-19 pandemic. As research suggests, its integration is highly dependent on the level of competence and willingness of usage, for it is the individual who ultimately decides to integrate ICT into their learning activities. The present study focuses on graduate students and teachers’ experiences of integrating ICT during the COVID-19 pandemic. Understanding the experience of these actors can bring insight into better ways to improve the design and implementation of professional development initiatives focused on ICT integration. In this study, the perceptions from students and teachers were collected through questionnaires and interviews analyzing their experience during the drastic transition from face-to-face sessions to remote learning. Results of this study suggest that, while ICT is accepted as the best possible alternative during the first period of the transition, students and teachers perceive a limited level of competence in instructional design. These results and its implications are discussed in view of guidelines for professional development initiatives.